Pantropical Response to Global Warming and the Emergence of a La Niña‐Like Mean State Trend. Issue 3 (3rd February 2020) - Lee, Sang‐Ki; Kim, Dongmin; Foltz, Gregory R.; Lopez, Hosmay
Abstract: A recent study by Zhang et al. (2019, https://doi.org/10.1029/2019GL084088 ) proposes "an interbasin ocean thermostat mechanism" to support the hypothesis that enhanced Indian Ocean warming during the past century has reduced the Pacific warming response to increasing greenhouse gases. In this commentary, we review the proposed mechanism in a broader perspective and discuss a potential role of Atlantic Ocean in modulating the future Pacific warming response to emphasize the interactive response of the pantropical atmosphere‐ocean to increasing greenhouse gases. Plain Language Summary: During the past century, the tropical Pacific Ocean has warmed significantly less than the other tropical oceans in response to increasing greenhouse gases. A recent study by Zhang et al. (2019, https://doi.org/10.1029/2019GL084088 ) proposes a new mechanism to help explain how enhanced Indian Ocean warming during the past century has reduced the Pacific warming response. In this commentary, we review the proposed mechanism in a broader perspective and discuss large‐scale atmospheric responses in the Indian, Pacific, and Atlantic basins and their interactions to increasing greenhouse gases. We also discuss how the future weakening of the Atlantic Ocean circulation may influence the Pacific warming response. Key Points: It remains debatable whether the Pacific SST response to increasing GHGs will be El Niño‐like or La Niña‐like in the future During the past century, enhanced Indian Ocean warming has reduced the Pacific warming via interbasin ocean thermostat mechanism A competing hypothesis involving Atlantic‐Pacific teleconnections is discussed to emphasize the pantropical response to increasing GHGs